Should the Central Sterile Supply Department in Every Hospital? - Dhian Kartikasari; Viera Wardhani (Universitas Muhammadiyah Yogyakarta, 2020)
Hospitals as health services should prevent the risk of infection for patients and hospital staff. One indicator of success in hospital services is the low number of nosocomial infections or Healthcare-Associated Infection. Efforts to reduce the incidence of nosocomial infections are by carrying out good Central Sterile Supply Department services. This study aims to describe the process of sterilization transition in Mitra Delima Hospital Malang from a decentralized system to a centralized system. This study uses a qualitative approach that is focused on the Sterilization Unit of General hospital of Mitra Delima Malang. The study was conducted in August-October 2019. This research was conducted using interviews, observations, document studies, and literature studies. Sterilization activities at Mitra Delima Malang General Hospital which is still decentralized, starting from the decontamination process to labelling in other units, it is necessary to have a plan to develop a Central Sterilization Installation that is in line with the needs of Mitra Delima Malang General Hospital and accordance with the regulations, guidelines, and standards of Installation Central Sterilization to achieve the ideal Central Sterilization Installation. Sterilization in hospitals should use a centralized system. With a centralized and independent sterilization system with other departments, hospitals can be efficient, economical, safe, and valid in implementing sterilization equipment. This also ensures that the sterilization process will be overseen by specialized staff and runs according to the standard operating procedures.